2019
DOI: 10.3389/fneur.2019.00025
|View full text |Cite
|
Sign up to set email alerts
|

The Different Clinical Features Between Autoimmune and Infectious Status Epilepticus

Abstract: Objective: The prognosis of status epilepticus (SE) is highly related to the underlying etiology. Inflammation of the central nervous system (CNS), including infection and autoimmune encephalitis, is one of the treatable conditions causing SE. The initial presentation of infectious and autoimmune CNS disorders can be quite similar, which may be difficult to differentiate at the beginning. However, treatment for these entities can be quite different. In this study, we aim to identify the differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Moreover, in the founding study of END-IT, 91.5% of the encephalitis group had infectious encephalitis [6]. However, autoimmune encephalitis had emerged as an important etiology of SE recently [17] and several studies including ours have shown that infectious and autoimmune encephalitis have similar prevalence among SE patients [18,19,20]. Thus, SE patients with autoimmune encephalitis may generally have better outcomes than predicated by END-IT.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, in the founding study of END-IT, 91.5% of the encephalitis group had infectious encephalitis [6]. However, autoimmune encephalitis had emerged as an important etiology of SE recently [17] and several studies including ours have shown that infectious and autoimmune encephalitis have similar prevalence among SE patients [18,19,20]. Thus, SE patients with autoimmune encephalitis may generally have better outcomes than predicated by END-IT.…”
Section: Discussionmentioning
confidence: 89%
“…Patients with anti‐GABABR encephalitis are vulnerable to SE 39 and refractory seizures 18 . For SE, timely immunotherapy is more effective than other therapies such as general anesthesia 40 . Intravenous administration and rapid drug titration may be helpful as necessary 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of AE relies on clinical symptoms, autoimmune tests, and, sometimes, the responses to immunotherapy (Zuliani et al, 2012; Graus et al, 2016). Although consensus diagnostic criteria (Graus et al, 2016) have been proposed for AE, the similarities of clinical symptoms between AE and infectious encephalitis frequently make initial clinical differentiation a challenging task (Lin et al, 2019). The autoimmune tests were limited by their availability and the time required for the results.…”
Section: Introductionmentioning
confidence: 99%